Analiza pomembnosti informacij za planiranje in vodenje proizvodnje v lesnih podjetjih - Novak, Boštjan (Zbornik gozdarstva in lesarstva, 2006)
In wood industry, three types of production are known: piecework, serial and mass production. The presented research attempted to determine which information was crucial for successful planning and running of an individual type of production. We confirmed the supposition that each of the mentioned types of production has its own specifics and that the sets of information necessary for decision-making in an individual type of production are therefore of different importance. The results of the research performed in twelve Slovenian wood industry companies show that the information is of the utmost importance for decision-making as far as planning and running the production is concerned. It would be quiet reasonable to take into account the results of the research when setting up information system in wood industry companies.
Keywords: lesna industrija; planiranje; proizvodnja; vodenje